Diagnosis and treatment of an excess vertical dimension malocclusion - Vaden JL; Williams RA (Dentitio, 2016)
The orthodontic clinician must use a careful differential diagnosis protocol for each patient who seeks his or her care. The diagnosis must analyze all three components of a malocclusion-facial, dental, and skeletal. Each component must be carefully studied and understood so that (1) the proper questions are asked and (2) the correct diagnostic decisions are made so that an effective treatment plan can be developed. Once the treatment plan is finalized, proper forces at appropriate treatment intervals must be utilized. If these concepts are used, most vertically compromised patients can be successfully treated with conventional orthodontics.